ANALISIS PELUANG PEMBELIAN REWORKED CLOTHING DALAM MENGIMPLEMENTASIKAN SDGs PADA GENERASI Z - Michelle Putri Baswara; Putu Ayu Pramitha Purwanti (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2025)
Reworked clothing refers to the process of taking existing garments or textiles and transforming them into new clothing. Wearing reworked clothing is one of the best ways to reduce fashion waste while creating unique and environmentally friendly apparel. Generation Z is a digital generation that tends to express themselves through the clothes they wear. This study examines the simultaneous and partial effects of the variables willingness to pay, acceptance, product quality, and understanding of the SDGs concept on the purchase intention of reworked clothing. The research was conducted on 100 respondents in South Jakarta who follow the Instagram account @make.them.jealous, using an online Google Form questionnaire, with data analysis performed using SPSS software. The study aimed to determine both the simultaneous and partial effects of the independent variables on the dependent variable. The results showed that willingness to pay, acceptance, product quality, and understanding of the SDGs concept have a significant simultaneous effect on the purchase intention of reworked clothing. However, willingness to pay does not have a significant partial effect, acceptance does not have a significant partial effect, product quality has a significant partial effect, and understanding of the SDGs concept has a significant partial effect on the purchase intention of reworked clothing. Reworked clothing refers to the process of taking existing garments or textiles and transforming them into new clothing. Wearing reworked clothing is one of the best ways to reduce fashion waste while creating unique and environmentally friendly apparel. Generation Z is a digital generation that tends to express themselves through the clothes they wear. This study examines the simultaneous and partial effects of the variables willingness to pay, acceptance, product quality, and understanding of the SDGs concept on the purchase intention of reworked clothing. The research was conducted on 100 respondents in South Jakarta who follow the Instagram account @make.them.jealous, using an online Google Form questionnaire, with data analysis performed using SPSS software. The study aimed to determine both the simultaneous and partial effects of the independent variables on the dependent variable. The results showed that willingness to pay, acceptance, product quality, and understanding of the SDGs concept have a significant simultaneous effect on the purchase intention of reworked clothing. However, willingness to pay does not have a significant partial effect, acceptance does not have a significant partial effect, product quality has a significant partial effect, and understanding of the SDGs concept has a significant partial effect on the purchase intention of reworked clothing. Keywords : Reworked clothing, purchase intention, Generation Z, product quality, SDGs